Hidrogeoquímica dos aquíferos costeiros no município de Icapuí - Ceará - Araújo, Karen Vendramini de (2024)
This work was carried out in the municipality of IcapuÌ - Cear· with the objective of evaluating the hydrogeochemical behavior of aquifers, seeking to understand the processes that control the chemical composition of groundwater. The Dunas, Barreiras, JandaÌra and AÁu aquifers occur in the area. The methodology encompasses well registration, water and sediment sampling, laboratory analyses, hydroclimatological balance, multivariate statistical analysis, hydrochemical classification, hydrogeochemical modeling and vulnerability to salinization due to marine intrusion analysis, using the GALDIT method. Multivariate statistical analysis allowed the selection of the variables of greatest significance in the composition of groundwater in the area. Two components represents the compositional variations, one associated with mineralization processes and one related to seasonality and water pollution process. Through the hydrogeochemical modeling was possible to identify that the chemical characteristics of groundwater in the area are controlled, mainly, by the weathering silicates and the dissolution of carbonates, with contributions from anthropogenic activities and marine influence. The application of the GALDIT methodology identified regions with medium and high vulnerability to salinization due to the advance salt wedge for the Dunas/Barreiras coastal aquifer system. These two levels of vulnerability were individualized based on the distance of the points in relation to the coast, the height of the water level above sea level and the rCl-/rHCO3- ratio, which represents the impact of marine intrusion. The combination of applied approaches contributed to a better understanding of the geochemical behavior of groundwater, demonstrating that the identified hydrogeochemical processes are compatible with the observed hydrochemical characteristics, since the most significant parameters identified through multivariate statistical analysis are those originating from minerals which are under a tendency to dissolve, thus being added to the solution, according to hydrogeochemical modeling, while the parameters of lesser significance are associated with minerals under a tendency to precipitation, and are consequently removed from the aqueous solution. For significant parameters not correlated to the geological framework of the area, the assessment of marine influence through analysis of vulnerability to salinization by saline intrusion made it possible to attribute their origin to marine aerosols